Five Years of Strategic Partnership: Experience, Results and Prospects - N. A. Volobuyev; A. I. Chernousenko (Vestnik MGIMO-Universiteta)
(to the fifth anniversary of signing of the Agreement on strategic partnership betweenthe Russian Technologies State corporation and MGIMO(U) the MFA of Russia).